Power in the New Testament - De Villiers, Pieter; Merz, Annette (Contributions to biblical exegesis and theology ;, 2021)
Influential research by authors like Foucault and Arendt revealed the significant role of power in shaping relationships in society and faith communities. This volume contributes to this research trend by analysing the formative role of power in early Christian documents and communities. An introductory essay investigates theoretical approaches to power and the nexus between power and religion. It functions as orientation for the exegetical analyses of individual texts in the rest of the volume. Two contributions analyse power dynamics in the Bible generally and nine others investigate its use in specific early Christian texts. They attend to the vocabulary of power as well as the networks and actors involved in the execution of diverse forms of power. They focus on how these dynamics operate specifically in the Gospels, Pauline texts and traditions and the Apocalypse. They show that power can be abusive and dangerous, but it also is a positive, restraining force.